2023
DOI: 10.1177/08850666231163141
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Inferior Vena Cava Filters for Venous Thromboembolism in Adults With Trauma: An Updated Systematic Review and Meta-Analysis

Abstract: Background: Trauma is an independent risk factor for venous thromboembolism (VTE). Due to contraindications or delay in starting pharmacological prophylaxis among trauma patients with a high risk of bleeding, the inferior vena cava (IVC) filter has been utilized as alternative prevention for pulmonary embolism (PE). Albeit, its clinical efficacy has remained uncertain. Therefore, we performed an updated systematic review and meta-analysis on the effectiveness and safety of prophylactic IVC filters in severely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 141 publications
0
3
0
Order By: Relevance
“…Nevertheless, the efficacy and safety of this approach in trauma patients remain unclear. The pooled estimate from RCTs demonstrated no significant difference between the prophylactic IVCF group and the control group in mortality (RR 1.44; 95% CI 0.86–2.43; low quality), PE (RR 0.27; 95% CI 0.06–1.28; low quality), and DVT (RR 1.18; 95% CI 0.58–2.40; low quality) [ 97 99 ]. Similarly, pooled estimates from observational studies demonstrated no clear association between the use of prophylactic IVCFs and the risks of mortality (RR 0.63; 95% CI, 0.3–1.31; very low quality) or DVT (RR 1.65; 95% CI 0.85–3.2; very low quality) [ 100 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the efficacy and safety of this approach in trauma patients remain unclear. The pooled estimate from RCTs demonstrated no significant difference between the prophylactic IVCF group and the control group in mortality (RR 1.44; 95% CI 0.86–2.43; low quality), PE (RR 0.27; 95% CI 0.06–1.28; low quality), and DVT (RR 1.18; 95% CI 0.58–2.40; low quality) [ 97 99 ]. Similarly, pooled estimates from observational studies demonstrated no clear association between the use of prophylactic IVCFs and the risks of mortality (RR 0.63; 95% CI, 0.3–1.31; very low quality) or DVT (RR 1.65; 95% CI 0.85–3.2; very low quality) [ 100 103 ].…”
Section: Resultsmentioning
confidence: 99%
“…Byrnes et al [112] reported 42 patients with traumatic ICI who subsequently developed thrombotic complications; ICI remained stable in 25 out of 26 patients who started therapeutic anticoagulation 13 days after the injury and bleeding signs slightly increased in only one patient. As an alternative, there are reports suggesting the use of inferior vena cava filter insertion together with pharmacological prophylaxis [113].…”
Section: Prophylaxis and Anticoagulant Resumption After Tbimentioning
confidence: 99%
“…Only if this proves impossible or ineffective, due to contraindications or recurring PE, is filter placement recommended [ 3 ]. While some small trials suggest short-term benefits of IVC filters in preventing PE after trauma surgery, conclusive evidence for long-term efficacy remains elusive due to the absence of large-scale randomized controlled trials [ 4 , 5 ]. This shows that IVC filter use can be associated with many complications, including thrombosis.…”
Section: Introductionmentioning
confidence: 99%